Development of quadruped walking locomotion gait generator using a hybrid method - Jasni, Farahiyah; Shafie, Amir Akramin (IOP Publishing, 2013)
The earth, in many areas is hardly reachable by the wheeled or tracked locomotion system. Thus, walking locomotion system is becoming a favourite option for mobile robot these days. This is because of the ability of walking locomotion to move on the rugged and unlevel terrains. However, to develop a walking locomotion gait for a robot is not a simple task. Central Pattern Generator (CPGs) method is a biological inspired method that is introduced as a method to develop the gait for the walking robot recently to tackle the issue faced by the conventional method of pre-designed trajectory based method. However, research shows that even the CPG method do have some limitations. Thus, in this paper, a hybrid method that combines CPG and the pre-designed trajectory based method is introduced to develop a walking gait for quadruped walking robot. The 3-D foot trajectories and the joint angle trajectories developed using the proposed method are compared with the data obtained via the conventional method of pre-designed trajectory to confirm the performance.